Health risk assessment of metal(loid)s in soil and particulate matter from industrialized regions: A multidisciplinary approach - Francová, Anna; Chrastný, Vladislav; Vítková, Martina; Šillerová, Hana; Komárek, Michael (Environmental pollution (Barking, Essex, 2020)
In this study, samples of soil and particulate matter obtained from the highly industrialized region of Ostrava, Czech Republic, are used for the toxicity evaluation of the selected metal(loid)s (Cd, Cr, Cu, Ni, Pb, Zn, As). We investigated the samples from sites supposedly affected the most by the local pollution sources using mineralogical techniques (XRD, SEM/EDS) to understand the solid speciation of the contaminants as the crucial factor affecting their release. Although the bulk composition was defined by common silicates and oxides that are rather resistant to leaching, the presence of tiny Ni, Pb, and/or Zn sulfate-like droplets indicated a potential increase of the solubility of these metals. In vitro tests simulating gastric and lung fluids were used to assess the exposure risk for humans, as well as metal(loid) bioaccessibility. Based on the results, the potential risk for the observed age group (3-year-old children) could be recognized, particularly in the cases of As, Pb and Cd for both oral and inhalation exposure. Arsenic exhibits high bioaccessibility (7.13-79.7%, with the median values of 10.6 and 15.6 for SGL and SLF, respectively), high daily intake (1.4- to 8.5-fold higher than the tolerable daily intake) and high concentrations in atmospheric PM10 (2.5 times the tolerable concentration in air). In contrast, Ni exceeded tolerable concentrations in the atmosphere up to 20-fold, but its bioaccessibility remained relatively low (0.1-22%), and Ni did not pose a major threat to human health. Cadmium, Pb and As originating from industrial activities and domestic heating have been suggested to be the most important pollutants (tolerable daily intake was exceeded by up to 74-, 34- and 8-fold for Cd, Pb and As, respectively).
Keywords: Metals, Heavy; pevné částice; Humans; Bioaccessibility; Metals; Environmental Monitoring; Soil Pollutants; látky znečišťující půdu; Atmospheric pollution; vystavení vlivu životního prostředí; půda; lidé; kovy; Human exposure; Particulate Matter; předškolní dítě; monitorování životního prostředí; těžké kovy; PM(10); Czech Republic; Inhalation; Ingestion; Environmental Exposure; Risk Assessment; Soil; Česká republika; Child, Preschool; hodnocení rizik